Strategic Management to Cultivate Islamic Boarding Schools’ Educational Quality: Blending Model Implementation - Aip Syarifudin; Muhibbin Syah; Cecep Sumarna; Erni Haryanti (Eduvest - Journal of Universal Studies, 2022)
This study aims to explore strategic management of Islamic Boarding Scholl in order to cultivate educational quality. The present study employed a qualitative study by using descriptive analytical approach. Two Islamic boarding schools were selected as the research sites namely Sabilunnajat and Al-Ulfah Islamic boarding schools, Ciamis Regency, West Java, Indonesia. The findings revealed that these two Islamic boarding schools were deemed capable to survive in a fairly tight competition. Moreover, there were several strategic steps undertaken by these two Islamic boarding schools to survive and contribute to the society. This alteration attempt is a conceptualization of Islamic boarding school management system referred to, in other words, as management strategy. After obtaining the results of field data from two research sites, the researcher will subsequently analyze and attempt to improve the management system in the two research sites. A good boarding school and the survived one is considered capable to answer the needs of the society which is in line with the terms where quality is something that meets needs. Afterwards, this study proposed a model knowledge of Islamic boarding school management system particularly the Blending Model of Management of Islamic Boarding Schools